2023
DOI: 10.55908/sdgs.v11i3.386
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Agricultural Enterprises with an Active Environmental Stance: Analysis of Inter-Organizational Management Accounting

Abstract: Objective: The purpose of the research is to investigate the concept of system sustainability in the framework of inter-organizational management accounting with particular attention to the environmental sustainability of agricultural enterprises. The study is aimed at researching the factors affecting the stability of the cooperative, understanding the mechanism for achieving sustainability, and developing an adaptive system of management accounting for environmental costs.   Methods: The research relies prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Researchers emphasize the need to develop organic agriculture (Nasiyev et al, 2022b;Khoruzhy et al, 2023) based on the use of organic fertilizers (Bayazitova et al, 2023;Nasiyev, 2013). Organic agriculture is a potentially more environmentally friendly alternative to conventional agricultural production and can play an important role in the sustainable development of ecosystems (Nokusheva et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers emphasize the need to develop organic agriculture (Nasiyev et al, 2022b;Khoruzhy et al, 2023) based on the use of organic fertilizers (Bayazitova et al, 2023;Nasiyev, 2013). Organic agriculture is a potentially more environmentally friendly alternative to conventional agricultural production and can play an important role in the sustainable development of ecosystems (Nokusheva et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This integration is pivotal in shaping how businesses approach their environmental impact and report it in their financial statements. Khoruzhy et al (2023) provide a compelling insight into this integration within the agricultural sector. Their research focuses on the development of an adaptive system of management accounting that emphasizes environmental costs.…”
Section: Environmental Costing Within the Framework Of Sustainable Ac...mentioning
confidence: 99%
“…This adaptation is not just a response to market demands but also a strategic move towards sustainable development. The research by Khoruzhy et al (2023) illustrates how environmental costing can be effectively incorporated into the management accounting systems of organizations, particularly those in sectors with significant environmental impacts. Sapozhnikova and Tkacheva (2021) delve into the environmental category of sustainable development reporting in corporations.…”
Section: Environmental Costing Within the Framework Of Sustainable Ac...mentioning
confidence: 99%
“…The third indicator is knowledge, where knowledge refers to an individual SSI owner's understanding of the notion of eco-friendly material selection for residents and the recycling process-for example, selecting materials that are eco-friendly and easy to recycle (Liudmila Khoruzhy et al, 2023). Batik SME and concluded that the natural extract could be reused until nothing is left over after the manufacturing process, so it does not cause waste, unlike synthetic or chemical waste.…”
Section: Implication Criteriamentioning
confidence: 99%